ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL PERBANDINGAN PADA PROSES PEMBELAJARAN DARING - Mega Dwi Cahyani; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study used descriptive qualitative method. This article aims to analyze errors in solving comparison questions for Class VII SMP students. The subjects studied were students of SMP IT Sukamanah class VII-C, with a total of 33 students. It consists of 22 female students and 11 male students. The data used in the study includes the results of the completion of the written test. The instrument of this written test is in the form of a description question that contains 5 questions. The analytical technique used in this research is by collecting data from the test instrument. The percentage of error in the low question indicator is to make a comparison worth to determine the value of x with a percentage of 20% and for a high question indicator is to explain problems related to the comparison with the percentage of 70%.